Faunal analysis of the species Anastrepha in the fruit growing complex Gaviao River, Bahia, Brazil - de Sa, Ricardo Falcao; Castellani, Maria Aparecida; Lopes Ribeiro, Ana Elizabete; Perez-Maluf, Raquel; Moreira, Aldenise Alves; Nagamoto, Nilson Satoru [UNESP]; do Nascimento, Antonio Souza (Alma Mater Studiorum, Univ Bologna, 2012)
Besides being considered the greatest pests of fruit growing, fruit flies constitute a large obstacle to the growth of the exportation of fresh fruit. Knowledge of the structure of fruit fly communities is of great importance to the bioecological studies of these insects, but there is a lack of information about the faunistic composition of fruit flies in Brazil. The objective of this work was to analysis the composition of the species of Anastrepha, in eleven mango orchards of the fruit growing complex Gaviao River, Bahia, Brazil. These studies were done in 2004 and 2005, in Anage, Caraibas and Belo Campo town, 23 McPhail traps, which collected 798 female fruit flies from the genus Anastrepha. The structure of these communities was evaluated in each orchard by means of faunistic indexes frequency, constancy, dominance, diversity and similarity. The number of species varied from four to eight in each orchard; and the following species was recorded: Anastrepha fraterculus (Wiedemann), Anastrepha obliqua (Macquart), Anastrepha dissimilis Stone, Anastrepha amita Zucchi, Anastrepha distincta Greene, Anastrepha pickeli Lima. Anastrepha sororcula Zucchi and Anastrepha zenildae Zucchi. The most frequent and dominant species were A. fraterculus and A. obliqua. The indexes of diversity varied from 1.01 to 1.62. In general, the similarity between orchards was high (above 55.0%). We observed the formation of groups, one constituted by Frutvale, Carlan, Santa Clara and Panorama orchards; another composed of Cofet, Campo Gaviao and Ouro Verde and a third group formed by Boa Vista orchard. Barra da Onca and Arruda are distinguished from other orchards.
Keywords: faunistic analysis; fruit fly; Mangifera indica; monitoring; similarity